The illusion of law: A philosophical and legal study - Melnikov, Victor Yu.; Seregin, Andrei V.; Cherkasova, Marina A.; Abramova, Marina A.; Hmelchenko, Elena G. (Opción, 2020)
The article examines the phenomenon of the legal illusion of the principle of equality and the reality of legal inequality via historical and legal, systemic, structural-functional, comparative-legal, statistical, sociological, specifically the formal-logical, logical-legal methods. As a result, the political and legal choice of the best form of the state and the variety of the legal family, in many respects, is secondary in the construction of the institution of private property. In conclusion, the state and law are idealistic (illusory) constructions in reality represented by power and law-realization practice.